Understanding Religious Moderation Perspectives of MAN Teachers in Aceh - Rafidhah Hanum; Lina Rahmalia (JURNAL AT-TURAS, 2025)
Intolerance is a problem faced by Indonesian society to this day. And to overcome this problem, educational institutions are one of the institutions that have an important role in instilling religious moderation. The purpose of this study was to obtain information about the knowledge of Madrasah Aliyah teachers in Banda Aceh and Aceh Besar about religious moderation and to find out the implementation of religious moderation in the teaching and learning process and what values of religious moderation are built by teachers at MAN Banda Aceh and Aceh Besar. This study used a qualitative approach with interview methods, observation, and document analysis to obtain data from the principal, teachers, and students. The results showed that teachers' understanding of religious moderation was generally good, especially for those who had attended training. Moderation values, such as justice (adl), balance (tawazun), simplicity (i'tidal), and unity and ukhuwah, were internalized through various learning methods, including discussion, group work, and field studies. However, there are several challenges in implementing religious moderation in madrasas, such as variations in teacher understanding, the dominance of lecture methods, and the influence of the social environment that still has conservative or extreme views. In addition, limited support for resources and ongoing training are also obstacles in optimizing the implementation of this concept. The implications of this study indicate that increasing teacher training, diversifying learning methods, and integrating religious moderation values in all subjects need to be done systematically. Support from madrasas and the government is needed to ensure that religious moderation values can be implemented effectively so that students can develop into inclusive, tolerant individuals who have a balanced understanding of religion.